2022
DOI: 10.1016/j.rser.2022.112197
|View full text |Cite
|
Sign up to set email alerts
|

Heat storage: Hydration investigation of MgSO4/active carbon composites, from material development to domestic applications scenarios

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…This type of composite is preferred in medium-and low-temperature TCES systems. After a compromise between the largest amounts of salt and the reaction heat, the activated carbon-MgSO 4 (30 wt.% MgSO 4 ) composite in the latest research [201] was proven to be better for completing eight cycles of adsorption/desorption stably (Figure 19d) and had a higher reaction enthalpy of 1324 kJ•kg −1 during adsorption. A new composite material hydroxyapatite-MgSO 4 containing two salt contents of 5 wt.% and 20 wt.% was prepared and characterized, and the results indicated that the porous matrix hydroxyapatite greatly improved the slow kinetics of MgSO 4 and considerably reduced the reaction time.…”
Section: Salt Content Of the Composite Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…This type of composite is preferred in medium-and low-temperature TCES systems. After a compromise between the largest amounts of salt and the reaction heat, the activated carbon-MgSO 4 (30 wt.% MgSO 4 ) composite in the latest research [201] was proven to be better for completing eight cycles of adsorption/desorption stably (Figure 19d) and had a higher reaction enthalpy of 1324 kJ•kg −1 during adsorption. A new composite material hydroxyapatite-MgSO 4 containing two salt contents of 5 wt.% and 20 wt.% was prepared and characterized, and the results indicated that the porous matrix hydroxyapatite greatly improved the slow kinetics of MgSO 4 and considerably reduced the reaction time.…”
Section: Salt Content Of the Composite Materialsmentioning
confidence: 99%
“…[211] Copyright © 2017 Elsevier Ltd. All rights reserved. [201], (e) MgCl 2 , (f) graphene oxide aerogel (rGOA)-MgCl 2 [207], (g) expanded vermiculite-K 2 CO 3 [208], (h,i) CaCl 2 -SBA-15 [209], (j,k,l) hydroxyapatite-MgSO 4 [150]: The red dotted line shows the floating range of energy density in (j), (m) silica gel-SrBr 2 [210], (n) silica gel-CaCl 2 [211]: Reprinted with permission from Ref. [110] Copyright © 2021 Elsevier B.V. All rights reserved; with permission from Ref.…”
Section: Salt Content Of the Composite Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…More generally, the current trend in novel material developments aims at the energy storage density enhancement [18]. The development of highperformance, cost-effective TCMs is crucial because they should be industrially and economically attractive (e.g., easily scalable, cost-effective) and prepared from renewable and abundant natural resources [20].…”
Section: The Adsorption Phenomenon and Related Materialsmentioning
confidence: 99%